2021
DOI: 10.1002/14651858.cd011589.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Routine provision of feedback from patient-reported outcome measurements to healthcare providers and patients in clinical practice

Abstract: DC et al. (14 more authors) (2021) Routine provision of feedback from patient-reported outcome measurements to healthcare providers and patients in clinical practice. Cochrane Database of Systematic Reviews, 2021 (10). ARTN CD011589.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 242 publications
5
61
0
1
Order By: Relevance
“…Implementation of the set could improve patient care by using innovative and multipurpose approaches, including clinical encounters, electronic health records, patient-reported outcome measures feedback, and others [38][39][40]. However, in practice, the utility of the standard set is still to be determined through ongoing evaluation of its implementation [41].…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of the set could improve patient care by using innovative and multipurpose approaches, including clinical encounters, electronic health records, patient-reported outcome measures feedback, and others [38][39][40]. However, in practice, the utility of the standard set is still to be determined through ongoing evaluation of its implementation [41].…”
Section: Discussionmentioning
confidence: 99%
“…PROs are direct reports from patients about symptoms, function or well-being with respect to a condition or treatment without interpretation by a clinician or anyone else [2]. Evidence suggests that using PROs in routine care may improve patient-clinician communication, quality of life, symptom burden, patient satisfaction and even survival [3][4][5][6][7]. In these cases, PROs are essentially used as screening tools to help identify problems for further discussion with a clinician that might otherwise go unaddressed.…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians’ and patients’ perceived benefits of using PROMs for individual patient management include patient involvement and personalized, holistic care [ 14 ]. Patient-facing PROM digital tools may support patient-clinician communication [ 15 ] and improve management of THA/TKA expectations [ 16 ], potentially increasing patient satisfaction with care experiences and health outcomes [ 17 ]. However, one study of a PROM-based feedback report in patients with hip or knee osteoarthritis found no meaningful between-group differences in patient activation, satisfaction, or perceptions of the physician–patient relationship [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, one study of a PROM-based feedback report in patients with hip or knee osteoarthritis found no meaningful between-group differences in patient activation, satisfaction, or perceptions of the physician–patient relationship [ 18 ]. A Cochrane review on PROM feedback across multiple clinical conditions also identified limited to no improvements in patient perceptions of self-efficacy, unmet needs, or satisfaction [ 15 ].…”
Section: Introductionmentioning
confidence: 99%